1974
DOI: 10.1139/x74-079
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and Nutrient Content of 4-year-old Fertilized and Unfertilized Northern Hardwood Stands

Abstract: Biomass and nutrient content of natural stands of northern hardwood regeneration were measured 4 years after clearcutting. Pin cherry and shrubs made up a significant proportion of the biomass in both unfertilized and fertilized stands. Yet these stands are well stocked with large numbers of desirable commercial species, especially paper and yellow birch. However, fertilizer greatly stimulated pin cherry to the detriment of the commercial species. Paper birch was the only commercial species to increase in aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In addition, LAI shows no significant correlation with height, FHD (either height grouping), successional status, understory development or any other variable strongly correlated with these. This is not surprising in view of recent studies strongly linking LAI to availability of moisture and nutrients (Grier and Running 1977, Safford 1974, Safford and Filip 1974. Total LAI appears more responsive to resource availability than to age, species composition or canopy structure.…”
Section: La!mentioning
confidence: 65%
“…In addition, LAI shows no significant correlation with height, FHD (either height grouping), successional status, understory development or any other variable strongly correlated with these. This is not surprising in view of recent studies strongly linking LAI to availability of moisture and nutrients (Grier and Running 1977, Safford 1974, Safford and Filip 1974. Total LAI appears more responsive to resource availability than to age, species composition or canopy structure.…”
Section: La!mentioning
confidence: 65%
“…Studies in the northeastern hardwood forest have shown that its competitive effect depends upon its density in relation to the species of interest. For yellow birch, Safford and Filip (1974) and Leak (1988) found a negative effect on survival and growth during the regeneration stage, but neither Heitzman and Nyland (1994) nor Ristau and Horsley (1999) found a negative effect. However, it is generally recognized that yellow birch has the ability to be codominant when pin cherry develops at intermediate densities (Wendel 1990).…”
Section: Vegetation Dynamicsmentioning
confidence: 84%
“…4b), and positive responses to P occurred at all but the highest fertilization rates, for which there are few observations. Some have reported increased foliar P concentrations with fertilization (Mercer 1974;Safford and Filip 1974;Ellis 1979;Safford and Czapowskyj 1986;Fahey et al 1998;Gradowski and Thomas 2008), indicating that fertilization did significantly increase P availability. However, others (Finn and White 1966;Schmitt et al 1981;Leech and Kim 1990;Ouimet and Fortin 1992) found no such increase, which is consistent either with Psufficiency in the control trees, or with insufficient P availability relative to other added nutrients.…”
Section: Production Responses To P Fertilizationmentioning
confidence: 99%